Tujuan Manajemen Pendidikan Islam - Sonia Purba Tambak; Anisa Maulidya; Khairani Khairani (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
Islamic Education Management is a management set to develop Islamic education and part of the management regarding the use of all existing resources in Islamic educational institutions, so that the goals can be achieved effectively, efficiently and productively. This study used a qualitative approach with library research. This study uses the thematic method (maudu'iy), namely the collection of verses of the Koran which discuss the objectives of Islamic education management. Sources of research data were obtained from verses of the Koran, interpretations and hadiths as well as books and journals. Data collection techniques by collecting literature data or library materials that lead to discussion in research. Data analysis was carried out by content analysis, namely content analysis which contains conclusions based on valid data by considering the contents of the writing. The purpose of this study is to analyze the verses and interpretations regarding the objectives of Islamic education management. The conclusion from this study there are five objectives of Islamic education management, namely planning educational programs according to Islamic law, preparing educational facilities and infrastructure according to the guidance of the Koran and hadith, managing educational institutions so that educational goals are achieved according to Islamic law, controlling the educational process based on al- -Quran and Hadith, improve resources in Islamic educational institutions. Keywords: Management Objectives, Management of Islamic Education, Tafsir of Management Verses